Euro Membership and Fiscal Reaction Functions - Alfons Weichenrieder; Jochen Zimmer (Center for Economic Studies and ifo Institute (CESifo), 2013)
The paper uses fiscal reaction functions for a panel of euro-area countries to investigate whether euro membership has reduced the responsiveness of countries to shocks in the level of inherited debt compared to the period prior to succession to the euro. While we find some evidence for such a loss in prudence, the results are not robust to changes in the specification, such as an exclusion of Greece from the panel. This suggests that the current debt problems may result to a large extent from preexisting debt levels prior to entry or from a larger need for fiscal prudence in a common currency, while an adverse change in the fiscal reaction functions for most countries does not apply.
Keywords: H62; E62; 330; debt sustainability; fiscal reaction function; euro area